Inflation in Romania: Causes, Effects, and Targeting Strategies - Razvan DOBREA, Catalin; Catalin CRETU, Romeo; Catalin MANESCU, Octavian; MONCEA, Madalina (European Journal of Sustainable Development, 2024)
Inflation is based on numerous partial causes, from the correlation of which the inflationary process results. elected, it will be shown what losses the company will suffer because it fired a person without notice, especially when he was on vacation. In this paper, we will follow the fact that inflation has a fixed increase, this being indexed and calculated at the level of Romania, by the National Institute of Statistics, to calculate the salary and commission due for the injured employee. In specialized literature, inflation is expressed in monetary terms by the fact that the prices of services and goods increase, and the purchasing power of a mounting unit decreases. Keywords: demand, cost, finance, inflation, Romania